Pembuatan Nanopartikel CaO dari Cangkang Telur Ayam Menggunakan Ekstrak Etanol Daun Salam (Syzygium polyanthum): Synthesis of CaO Nanoparticles from Chicken Eggshells Using Ethanol Extract of Bay Leaves (Syzygium polyanthum) - Mellida Yani; Gladys Ayu Paramita Kusumah Wardhani; Agus Taufiq (LPPM Universitas Mataram, 2023)
Chicken eggshell waste contributes to environmental because it have CaCO3 content. Calcium carbonate in chicken eggshells is used as a basic material in the synthesis of CaO nanoparticles through a calcination process at 900oC. CaO nanoparticles have unique characteristics that make them are needed for various fields of application such as environment, materials, and biomedicine. In addition, the synthesis of these nanoparticles can reduce the use of hazardous and environmentally friendly chemicals. This method has been widely used as an alternative method, one of which utilizes secondary metabolites found in ethanol extract of bay leaves as reducing and stabilizing agents. This research was conducted with 3 volume variations of bay leaf extract with calcined eggshell base materials, namely 3:7, 5:5, and 7:3 (v/v) to determine the effect on the resulting particle size. Characterization of CaO nanoparticles using UV-Vis, FTIR, and SEM. The nanoparticles obtained were in the form of white fine powder. The characterization results show the maximum absorption of CaO nanoparticles at λ 215 - 270 nm. Based on the FTIR spectra, Ca-O bonds can be identified in the three variations at 712 cm-1 dan 514 cm-1 and 874 cm-1 shows Ca-O-Ca bond. The resulting material has a flake shape and agglomeration morphology with an average particle size range of 43-498 nm.